Development of Diclofenac Sodium 3D Printed Cylindrical and Tubular-Shaped Tablets through Hot Melt Extrusion and Fused Deposition Modelling Techniques - Tryfon Digkas; Alina Porfire; Jeroen Van Renterghem; Aseel Samaro; Gheorghe Borodi; Chris Vervaet; Andrea Gabriela Crișan; Sonia Iurian; Thomas De Beer; Ioan Tomuta (Pharmaceuticals, 2023)
The present study aimed to develop 3D printed dosage forms, using custom-made filaments loaded with diclofenac sodium (DS). The printed tablets were developed by implementing a quality by design (QbD) approach. Filaments with adequate FDM 3D printing characteristics were produced via hot melt extrusion (HME). Their formulation included DS as active substance, polyvinyl alcohol (PVA) as a polymer, different types of plasticisers (mannitol, erythritol, isomalt, maltodextrin and PEG) and superdisintegrants (crospovidone and croscarmellose sodium). The physicochemical and mechanical properties of the extruded filaments were investigated through differential scanning calorimetry (DSC), X-ray diffraction (XRD) and tensile measurements. In addition, cylindrical-shaped and tubular-shaped 3D dosage forms were printed, and their dissolution behaviour was assessed via various drug release kinetic models. DSC and XRD results demonstrated the amorphous dispersion of DS into the polymeric filaments. Moreover, the 3D printed tablets, regardless of their composition, exhibited a DS release of nearly 90% after 45 min at pH 6.8, while their release behaviour was effectively described by the Korsmeyer–Peppas model. Notably, the novel tube design, which was anticipated to increase the drug release rate, proved the opposite based on the in vitro dissolution study results. Additionally, the use of crospovidone increased DS release rate, whereas croscarmellose sodium decreased it.